ПИЛОТНЫЙ ПРОЕКТ ПО СОЗДАНИЮ ООПТ У КАЗАХСТАНСКОГО ПОБЕРЕЖЬЯ КАСПИЙСКОГО МОРЯ С ЦЕЛЬЮ СОХРАНЕНИЯ КАСПИЙСКОГО ТЮЛЕНЯ (ҚазҰУ хабаршысы. Экология сериясы, 2016)
The authors have analyzed data on numbers of Caspian seal and main riskfactors of Caspian seal survival. Prospective sites within the Caspian Sea within its Kazakhstan sector for establishment а special protected natural areas (SPNAs) have been proposed: ice floe in the Northern Caspian, Kulaly archipelago, Komsomolots gulf, Bautino bay, Kenderli gulf, migration corridor along the coastline at depths up to 50m.